please solve

Asked by nmenghani | 12th May, 2010, 09:15: PM

Expert Answer:

9(x2+1/x2)-9(x+1/x)-52 = 0

9(x2 + 2 + 1/x2 -2)-9(x+1/x)-52 = 0

9((x + 1/x)2 -2) - 9(x + 1/x) - 52 = 0

9(x + 1/x)2 - 9(x+1/x) - 70 = 0

9Y2 - 9Y - 70 = 0

Y = -7/3 and 10/3.

x + 1/x = 10/3

3x2 - 10x + 3 = 0  

x = 2/3 and 6.

Similarly we can obtain the x values for Y = -7/3.

Regards,

Team,

TopperLearning.

Answered by  | 18th May, 2010, 09:14: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.